Exploring the functions of the human body - Lancraft, Thomas ([S.1.] : J. Wiley & Sons, 2006)
Focuses on the examination of physiological processes within each system of the body, using animations, tutorials, interactivity, and clinical correlations to enhance student understanding
vol. 1. Gas exchange and pH balance: the respiratory system vol. 2. Energy acquisition and use: the digestive system and metabolism vol. 3. Disease resistance: the lymphatic, integumentary and immune systems vol. 4. Continuity: the reproductive systems and development
Title from disc label
System requirements for Windows: Pentium 166 or higher; 32MB RAM; Windows 95, 98, ME, NT, 2000, or XP; 4x speed CD-ROM drive; 800 x 600 screen resolution, hi-color mode; sound card; Internet Explorer v5.0 and above or Netscape Navigator v4.7x
System requirements for Macintosh: PowerPC G3/233MHz; 64MB RAM; Mac OS 8.1 and 9.x; 4x speed CD-ROM drive; 800 x 600 resolution, 256 colors; Netscape Navigator v4.7x
Keywords: Human physiology; Anatomy; Physiology